Convenience and short comings among paediatric cochlear implant candidates - Hossain, Mohammod Delwar; Mahboob Hasan, M.; Uddin, Mohammad Taslim; Islam, Mohammed Sirazul; Ahamed, Shamem (International Journal of Research in Medical Sciences, 2023)
Background: Cochlear implants have revolutionized the treatment of severe-to-profound sensorineural hearing loss in children. However, the convenience and shortcomings experienced by pediatric cochlear implant candidates in various settings remain understudied. This study aimed to assess the convenience and shortcomings among pediatric cochlear implant candidates in home, school, and other social settings. Methods: This was a prospective clinical study that was conducted in the Cochlear Implant (CI) Center, Combined Military Hospital (CMH), Dhaka and Chattogram, Bangladesh from July 2015 to December 2022. A total of 200 parents of pediatric cochlear-implanted children were enrolled in this study as the study subjects. A simple random sampling technique was used in sample selection. All data were processed, analyzed, and disseminated by using MS Excel and SPSS version 22.0 program as per necessity. Results: The study analyzed information collected during the study period, focusing on the convenience and shortcomings reported by the parents of cochlear implant recipients. The findings revealed that the highest level of convenience was reported in some other social settings (82.84%), followed by home (75.67%) and school (64.4%). In contrast, shortcomings were reported primarily in the home environment (63.6%), followed by school (34.6%) and other social settings (31.45%). Conclusions: In the majority of cochlear implant children, convenience is observed in some other social settings than home or school. In the majority of cochlear implant children, shortcomings are observed in their homes.